Increasing Employee Performance through Motivations and Work Discipline in UPPKH Bandung City - Hertina, Dede; Septiani, Dian (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
The purpose of this study is to examine and analyze the influence of motivation and work discipline on employee performance. Data collection was carried out by distributing questionnaires, the population of this study was the UPPKH Bandung City, amounting to 60 by using purposive sampling obtained a sample of 58. This research method uses a quantitative descriptive approach. The results showed that simultaneously motivation and work discipline have an effect on employee performance. This is evidenced by the results of the simultaneous test and partial test. Therefore, the test results of this study indicate that there is a simultaneous influence between motivation and work discipline variables on the performance of employees in UPPKH Bandung City.